Raziskava redčenj bukovih sestojev v raziskovalnih objektih Pišece in Brezova reber - Saje, Robi (Gozdarski vestnik, 2013)
For the study of effects of beech stands thinning, two research sites (Pišece and Brezova reber) were selected and divided into three blocks, each block wasdivided into three plots (plot area 0.09 ha), which were randomly assigned to treatment: classical selective thinning (treatment A), selective thinning with fixed crop trees (treatment B) and control plots for natural development (treatment C). During the first measurements we established the stand parameters. In stands with A and B treatment we selected crop trees and their competitors for cut. Measurement limit was DBH = 5 cm in Brezova reber and DBH= 10 cm in Pišece. We registered 3.759 trees ha-1 in Brezova reber and 1.533 trees ha-1 in Pišece. Growing stock for stands in Brezova reber was from 40 to 179 m3 ha-1, basal area from 20.9 to 32.5 m2 ha-1, and in Pišece from 119 to 317 m3 ha-1 and from 16.9 to 35.3 m2 ha-1. In the stands with treatment A in Brezova reber we selected on average 467 crop trees ha-1and 1.276 competitors ha-1 were cut down (28.4 % of the growing stock); in stands in Pišece we selected 274 crop trees ha-1 and cut down 530 competitors ha-1 (31.5 % of the growing stock). In the stands with treatment B in Brezova reber, we selected on average 100 crop trees ha-1 and 496 competitors ha-1 were cut down (17.9 % of the growing stock); in Pišece we selected 89 crop trees ha-1 and cut down 326 competitors ha-1 (24.0 % of the growing stock). Using parametric tests, we found differences between the A and B treatments in the number of selected competitors per crop tree and in the share of the competitors in the total stand.
Keywords: redčenje; nega gozdov; bukovi sestoji; raziskovalne ploskve